The Effect of SiC and Cu Weight Fraction on the Characteristics of Al 6061 Composite - Sumarji Sumarji; Danny Febriansyah; Mahros Darsin; Wazirotus Sakinah; R. Puranggo Ganjar Widityo (Politeknik Negeri Lhokseumawe, 2023)
Composites are made of multiple materials that are combined to create new materials with better properties. The purpose of this study is to determine the effects of SiC and Cu weight fractions on hardness, tensile strength, microstructure and scanning electron microscopy (SEM) of Al 6061 composites. The manufacturing method used for creating composites in this study was stir-casting. Each composite component and its functions are as follows: aluminum 6061 as the matrix, silicon carbide (SiC) as a reinforcement, and copper (Cu) functions to improve the characteristics of the composite. Variations were made by weight composition of SiC (1%, 3%, and 5%) and Cu (5% and 8%). Observations were carried out on their hardness, tensile strength, and microstructure; each of which using Rockwell hardness test B (ASTM E 18 standard), a multipurpose tensile testing machine, and SEM, respectively. The results of this study indicate that the addition of SiC and Cu affects the aluminum 6061 characteristics. The best result of the hardness test was shown at Al6061 + 5% SiC + 8% Cu (109.37 HRB). The best tensile strength (UTS) test result was shown at Al6061 + 5% SiC + 8% Cu (211.8 MPa) with elongation number of 2.8%. There has been a significant reduction in grain size under micro observations that occurred very well but was still relatively not uniform. The result of several SEM observation phases formed by the combination of Al6061 and the addition of 5% SiC + 5% Cu and 8% Cu showed an observation phase of AlZnMgCu, α (Al) + AlZnMgCu, Al2Cu, and Al2CuMg.